Student Counsellors' Perspectives on Comprehensive Prevention and Intervention Strategies for Adolescent Internet Addiction - Suryani Suryani; Restuning Widiasih; Cecep Eli kosasih; Windy Rakhmawati; Habsyah Saparidah Agustina (Iranian Journal of Psychiatry)
Objective: This study aimed to explore the perspectives of student counsellors regarding comprehensive prevention and intervention strategies for addressing internet addiction among adolescents. Method: This study employed an exploratory-descriptive qualitative design. Data collection involved focus group discussions (FGDs) with 12 purposively selected student counsellors from high schools in four West Java regions. Counsellors were chosen based on their experience in managing students with internet addiction within the past year. FGDs were conducted virtually due to Covid-19 restrictions, with sessions aimed at exploring perceptions and strategies related to internet addiction prevention and intervention. Data were analyzed using thematic analysis following Clarke and Braun's approach to identify key themes. Results: The results of the study obtained 5 themes which are: a comprehensive assessment is needed to determine appropriate interventions for students experiencing internet addiction; family is the main supporting factor in managing and preventing internet addiction; various parties must cooperate in overcoming internet addiction; health education about internet addiction during school orientation is important as a prevention program; and digitalization and communication control programs affect the phenomenon of internet addiction. Conclusion: Based on the results of this study, we can conclude the importance of comprehensive assessments to determine appropriate interventions and the need for support from other parties in overcoming internet addiction among students.